Colovesical Fistula due to Sigmoid Diverticulitis - Christos K. Stefanou; Spiridon Gkogkos; Stefanos Flindris; Apostolis K. Paxinos; Thomas Tsiantis; Polyxeni Oikonomou; Kostas Tepelenis; Stefanos K. Stefanou (Case Reports in Surgery)
Introduction. The incidence of colonic diverticulosis has risen significantly. Diverticular disease is the most frequent cause of colovesical fistulas, which are uncommon complications of diverticulitis. Clinical signs, such as fecaluria and pneumaturia, are typically required to confirm its presence. Finding the cause of the disease so that the proper therapy can be started is the primary goal of a diagnostic workup rather than observing the fistula tract itself. Case Presentation. We present a 43-year-old man complaining of frequent urinary tract infections for six months. On CT abdomen and pelvis, a colovesical fistula was diagnosed. Surgery was performed, and after the division between the sigmoid colon and the bladder, a sigmoidectomy and an end-to-end colorectal anastomosis were performed. During the surgery, the fistula tract was not detected. The patient was discharged in excellent condition on day six, and the catheter was removed on day 10. Conclusion. In conclusion, as in our case, any patient with a urinary tract infection should be suspected of having this condition, especially if he has persistent symptoms that have not responded to standard medical care. Patients who present with fecaluria, pneumaturia, and other specific symptoms of a colovesicular fistula do not necessarily need a barium enema or cystography to confirm the presence of the fistula.